KKN Care: Developing a Tahfidz House in Koto Baru Village - Febri Oza; Muhammad Yusuf Salam; Dasmawar Sinta; Vann Sok (Yayasan Adra Karima Hubbi, 2025)
ABSTRACTBackground. Community service program is a place for students to apply the knowledge and skills obtained in the lecture bench directly to the community. One form of community service carried out by community service program students is the development of tahfidz houses.Purpose. This study aims to explore the effectiveness of the community service program program in fostering Rumah Tahfidz to facilitate learning of the Qur'an and produce a generation of Qur'an memorizers.Method. This study uses a qualitative approach with case studies, involving data collection through participatory observation and in-depth interviews with community service program participants and the management of the Al-Qur'an Tahfidz House.Results. The results of this study indicate that the community service program is effective in improving understanding and memorization of the Qur'an among children, by increasing active participation in learning activities and religious life. Conclusion. The construction of a tahfidz house is one of the community service program programs that is useful and can be used as a model in implementing religious values in the daily lives of the younger generation.